-7(t-8)-3(3t+1)=-11

Simple and best practice solution for -7(t-8)-3(3t+1)=-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(t-8)-3(3t+1)=-11 equation:


Simplifying
-7(t + -8) + -3(3t + 1) = -11

Reorder the terms:
-7(-8 + t) + -3(3t + 1) = -11
(-8 * -7 + t * -7) + -3(3t + 1) = -11
(56 + -7t) + -3(3t + 1) = -11

Reorder the terms:
56 + -7t + -3(1 + 3t) = -11
56 + -7t + (1 * -3 + 3t * -3) = -11
56 + -7t + (-3 + -9t) = -11

Reorder the terms:
56 + -3 + -7t + -9t = -11

Combine like terms: 56 + -3 = 53
53 + -7t + -9t = -11

Combine like terms: -7t + -9t = -16t
53 + -16t = -11

Solving
53 + -16t = -11

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-53' to each side of the equation.
53 + -53 + -16t = -11 + -53

Combine like terms: 53 + -53 = 0
0 + -16t = -11 + -53
-16t = -11 + -53

Combine like terms: -11 + -53 = -64
-16t = -64

Divide each side by '-16'.
t = 4

Simplifying
t = 4

See similar equations:

| (2x-5)=(x+3) | | 4x^2-35x-375=0 | | 2(x-1)-(3x-5)=2(3x-1)-16 | | 15m^2=cm^2 | | X^2=4-4x | | R+t-8r+13t= | | X^2=2-2x | | (7*1.363636364-2)=(-4*1.363636364+13) | | 0.2x+0.5(13-x)=3.2 | | 3(x-y)-2(y-x)= | | (7x-2)=(-4x+13) | | 7x=4(x-8)+3x | | 0.2x+0.5(13-x)=3.8 | | -u^2+8u-16=0 | | 5(a-b)-2(a-b)+8(a-b)= | | (9x+5)=(11x-25) | | 10000*3.12= | | 88=(5+2y)*y | | 3(2b-a)-(2a-b)= | | (X^2+2x+40)=(x^2)-x+190 | | m(x)=x^5-10x^4+25x^3 | | 8(x+y)+3(x+y)= | | 4a+7a=9 | | 4.5x-1.8=3.2x+0.8 | | X^2=3+x | | z+2.6z-5.5=(z-0.3) | | 6(x-y)-3(3x+y)= | | -4.2-6y-4.7-2y=-7y-1.3 | | 4x-12=-48 | | 4(y-7x)-y= | | 5z=18z | | 5z=8z |

Equations solver categories